Association between physicochemical parameters and presence of pathogenic indicator microorganisms in mud crab - Arif Luqman, bin Shah Bani (Universiti Malaysia Sarawak (UNIMAS), 2015)
The incidence of food borne illness have increased globally in recent years, which could be partly attributed to environmental pollution. Changes in environment from their natural state may have an effect on pathogenic microbial content in seafood. This project was done in order to study the relationship between selected physicochemical parameters of local habitats of mud crab and presence of three pathogenic indicator bacteria. Thirteen mud crabs from three different sources were sampled then tested for their Aerobic Plate Count (APC) and specific detection using PCR for the presence of Salmonella typhimurium, Vibrio cholerae, and Escherichia coli 0157:H7. Temperature, pH, Dissolved Oxygen (DO) and Biochemical Oxygen Demand (BOD) of their habitats were also tested. Out of three sample's sources, crabs from Pendam River, Asajaya has the least favorable level of DO and BOD according tQ the national standard and also possess the highest plate count, which were for presumptive S. typhimurium was 5.0x 106 CFU/mL, V. cholerae is 5.2 x 106CFU/mL and E. coli is 4.4 x 107 CFU/mL. However, when tested with PCR, there were no presence of these targeted species. In conclusion, there was an association between physicochemical parameters of water and presence of pathogenic indicator microorganisms in crab.